PENGARUH MODEL PROBLEM BASED LEARNING BERBASIS TPACK BERBANTUAN ARTIFICIAL INTELLIGENCE TERHADAP HASIL BELAJAR SISWA DI SEKOLAH DASAR - Nabilah, Nabilah; Nanda, Nanda; Evi Syarah, Evi Syarah; Irmawati M; Husnul Khatimah, Husnul Khatimah; Asmirinda Resa, Asmirinda Resa; Intan Fandini, Intan Fandini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the effect of the application of the Problem Based Learning (PBL) model based on Technological Pedagogical Content Knowledge (TPACK) assisted by Artificial Intelligence on student learning outcomes in elementary schools. This study uses a quantitative approach with an experimental method through the One Group Pretest Posttest Design. The sample in this study amounted to 23 students at SDN No. 24 Inpres Saleppa. The data collection technique is carried out through the provision of learning outcome tests which are carried out before (pretest) and after (posttest) treatment. The research data was analyzed using descriptive and inferential statistical techniques. The results of the descriptive analysis showed an increase in the average score of student learning outcomes from 48.70 during the pretest to 70.43 during the posttest. Based on the results of the normality test, the research data was not normally distributed, so hypothesis testing was carried out using the Wilcoxon Signed Rank Test. The results of the hypothesis test showed a significance value of 0.001 (<0.05), which indicated a significant difference between learning outcomes before and after treatment. Thus, it can be concluded that the application of the TPACK-based PBL model assisted by Artificial Intelligence has an effect on improving student learning outcomes. This learning model encourages active involvement of students in the learning process through problem-solving activities and the use of technology that supports the achievement of more interactive and meaningful learning. Therefore, this model can be used as an alternative learning strategy that is effective in improving student learning outcomes in elementary school.